Analisis Bangkitan Perjalanan Berbasis Rumah Tangga pada Perumahan Bumi Tamanlarea Permai Kota Makassar - Sandy Nikolas Putra; Rais Rachman; Monika D.M Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
Bumi Tamalanrea Permai Housing is a residential area located in the eastern part of the city. This housing includes large-scale housing around 74 thousand inhabitants. This housing complex has a population that is heterogeneous in terms of socio-cultural, occupational and income levels. The purpose of the research is to model the trip generation of workers in the Bumi Tamanlanrea Permai (BTP) housing complex in Makassar City by taking the travel case in Blocks A, B, L and M.The results showed the characteristics of the population in BTP (Bumi Tamalanrea Pemai) housing are the number of family members, the number of motorcycle ownership, the number of car ownership, the amount of family income, the number of family members who work. The choice of workers' vehicles to take a motorcycle trip is still the most preferred choice for work. In this housing trip generation is influenced by the number of motorcycle ownership, the number of family members who work and the number of family members who attend school / college has a positive effect on the number of trip generation.